Experimental induction and monitoring of liver abscesses in cattle with ultrasonography - K.F. Lechtenberg; T.B. Avery; Tiruvoor G. Nagaraja (Kansas Agricultural Experiment Station Research Reports, 1988)
We have demonstrated that ultrasonography can be used to visualize liver abscess in live cattle. We have also developed a nonsurgical method of catheterizing the bovine portal vein and experimentally inducing liver abscesses by inoculating the portal vein with Fusobacterium necrophorum bacteria.
Keywords: Kansas Agricultural Experiment Station contribution; no. 88-363-S; Cattlemen' s Day; 1988; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 539; Beef; Liver abscess; Ultrasonography